Reducing Perioperative Risks of Surgery in Crohn's Disease - Reindl, Wolfgang (Visc Med, 2019)
BACKGROUND: Approximately one-third of all patients suffering from Crohn's disease (CD) undergo surgery within the first 10 years after diagnosis and another 20% will have a second operation in the 10 years after their first operation. Surgery will remain an essential part of managing CD and therefore it is crucial to prevent perioperative complications by optimizing perioperative management. METHODS: We reviewed the current literature on managing immunomodulating therapy, nutritional support, and thromboembolic prophylaxis in the perioperative situation. RESULTS: CD patients with serious nutritional deficits (weight loss >10% in the last 3–6 months, body mass index <18.5 kg/m2, or albumin levels <30 g/L) benefit from intensive enteral or parenteral nutritional support, thereby reducing the risk of surgical-site infections and post-operative septic complications. Immunosuppressive therapy with prednisolone doses >20 mg should be avoided. The risk of therapy with anti-TNFα agents, vedolizumab, and ustekinumab for surgical complications has not been fully established. Analysis of currently available data suggests that an interval of 4–8 weeks is prudent to avoid complications and reduce risk by performing protective ostomy in the emergency setting. Finally, due to the high risk of venous thromboembolism, prophylactic therapy with heparin is recommended. CONCLUSION: As most cases of CD-related surgery are performed in a non-emergency setting, careful planning and risk management can reduce the rate of surgical complications, increase quality of life, and also reduce costs.